2016
DOI: 10.15580/gjsetr.2016.3.052416098
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the use of Electric Generators: An Operative Model of Distance and Greening Buffers

Abstract: Against the background of the incessant electric power failure and the extensive use of electric power generator, the study investigates the use of electric power generators; so as to proffer ecologically sustainable mitigation strategies. The relative incidence of generator use was appraised. Residents coping mechanism as well as its efficacy were also assessed. Across the three recognizable residential densities of the city having 20 political wards, 50 urban blocks (10%) were sampled. A questionnaire was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(12 reference statements)
1
2
0
Order By: Relevance
“…The background noise varied disproportionately in buildings across the zones with the core zone having 47.3 -63.5 dB. Results of the outdoor noise levels obtained from the noise measurement were also supported by findings of past studies of Stanley et al, (2016) which got 85.13 dB for the outdoor noise; John et al, (2016); Akindele and Adejumobi (2016) and Osagie et al, (2018) which got comparably higher levels of noise than the permissible limits during the use of generators.…”
Section: Outdoor Noise Levels Of Generators In the Residential Buildingssupporting
confidence: 75%
See 1 more Smart Citation
“…The background noise varied disproportionately in buildings across the zones with the core zone having 47.3 -63.5 dB. Results of the outdoor noise levels obtained from the noise measurement were also supported by findings of past studies of Stanley et al, (2016) which got 85.13 dB for the outdoor noise; John et al, (2016); Akindele and Adejumobi (2016) and Osagie et al, (2018) which got comparably higher levels of noise than the permissible limits during the use of generators.…”
Section: Outdoor Noise Levels Of Generators In the Residential Buildingssupporting
confidence: 75%
“…Saber (2014) investigated noise pollution level in different environments in Erbil City and showed that in 177 sites that were examined, the indoor and outdoor sound pressure level were 87 dB and 105 dB respectively and thus caused hearing impediments; Salawu et al, (2015) carried out assessment and control of near-field noise levels of the 650 VA power generator in a residential building in Moro Local Government of Kwara State, Nigeria and found that such generating sets should be positioned at least 3 meters away from buildings in order to be safe for use; Sellappan (2013) carried out a study on noise impacts associated with power generators used in construction activities of DCT project and found that the noise levels produced by them were much higher than the permissible limit while Peter (2013) investigated noise pollution in laboratory buildings and showed that noise from devices used in the laboratory that can lead to a variety of medical issues for the laboratory personnel can be reduced by selecting systems that are specifically designed with noise reducing components. Studies of Akindele and Adejumobi (2016); and Osagie et al, (2018) on noise levels of generators in south southern part of Nigeria found sound pressure level above the set limit.…”
Section: Introductionmentioning
confidence: 91%
“…It was projected to reach 950.7million (N332.7billion at a current exchange rate of N350/$1) by 2020 [8]. The following population of some Nigerian cities uses power generators -66.6% of Benin, Edo State [9]; 73.2% of Ayingba, Kogi State [10]; 89.9% of Kaduna [11]; 84.9% of Port Harcourt [12]; 54% of Lagos and Osun States [13]; 78.6% of Ogbomosho, Oyo State [14]; and 72.9% of Nnewi North LGA, Anambra State [15]. Nationally, over 86% and 25% of Nigerian businesses and households, respectively have power generators [16].…”
Section: Introductionmentioning
confidence: 99%